Functional importance of the Gly cluster in transmembrane helix 2 of the Bordetella pertussis CyaA-hemolysin: Implications for toxin oligomerization and pore formation - Sirikran Juntapremjit (2018)
© 2015 Published by Elsevier Ltd. Adenylate cyclase-hemolysin (CyaA) is a major virulence factor of Bordetella pertussis causing whooping cough in humans. We previously showed that two transmembrane helices (α2 and α3) in the hemolysin domain (CyaA-Hly) are crucially involved in hemolytic activity. Here, PCR-based substitutions were employed to investigate a potential involvement in hemolysis of a series of four Gly residues (Gly530, Gly533, Gly537and Gly544) which map onto one face of a helical wheel plot of pore-lining helix 2. All CyaA-Hly mutant toxins were over-expressed in Escherichia coli as 126-kDa soluble proteins at levels comparable to the wild-type toxin. A drastic reduction in hemolytic activity against sheep erythrocytes was observed for three CyaA-Hly mutants, i.e. G530A, G533A and G537A, but not G544A, suggesting a functional importance of the Gly530-Gly533-Gly537cluster. A homology-based structure of the α2-loop-α3 hairpin revealed that this crucial Gly cluster arranged as a GXXGXXXG motif is conceivably involved in helix-helix association. Furthermore, a plausible pore model comprising three α2-loop-α3 hairpins implicated that Gly530XXGly533XXXGly537could function as an important framework for toxin oligomerization. Altogether, our present data signify for the first time that the Gly530-Gly533-Gly537cluster in transmembrane helix 2 serves as a crucial constituent of the CyaA-Hly trimeric pore structure.